Relationship between Vegetables and Fruit Consumption Habits, Nutrition Intake, Physical Activity, and Family Support with Adolescent Nutritional Status - Nanda Rizkha Heratama; Kusnandar; Suminah (International Journal of Science and Society, 2021)
Adolescents nutritional status is one of the major challenges for health workers and society, which is caused by their excessive intake of food, but lack of fiber intake and lack of physical activity. This research is to know how relationship between vegetables and fruit habits, nutrition and family support with adolescent nutritional status. This research design used was cross sectional, where research is conducted one-time to find relationships between the independent variable and the dependent variable. Its samples consisted of 340 adolescents in Pangkalpinang city. Subjects were screened by using google form first, data collection is done directly with the help of enumerators. The results of statistical tests showed that the habit of consuming vegetables (p = 0.005) and physical activity (p = 0.016) were the variables that had the most influence on adolescent nutritional status. Adolescents who often consume vegetables and have a minimum physical activity of 600METs / day have the opportunity to have a good nutritional status.